IDENTIFIKASI DAN PEMETAAN STAKEHOLDER DI PANGKALAN PENDARATAN IKAN SODOHOA KOTA KENDARI PROVINSI SULAWESI TENGGARA - Sitti Aisyah; Sarini Yusuf; Sjamsu Alam Lawelle (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
The aim of toe study was to identify stakeholder, to know structure according to stakeholder namber, stakeholder mapping and to analysis significant affect among stakeholder in trade and non-trade activity in UPTD PPI-TPI Sodohoa of Kendari. The method used in the study was survey method. Samples was choosen by purposive technique accidental sample. Tool analysis used was the power interest legitimacy and the venn diagram analysis. The results of this study showed that there were 22 stakeholders with 6 categories namely PIL (power interest legitimacy), PL (power legitimacy), PI (power interest), P (power), I (interest) and others. The PIL category much involved in all activities such as head of PPI, head of audted of PPI, enterprise of CV. Alfaraya, fisherman group, ice crusher group, and fisherman shop. The PL category is PPI staff or employee, park employee and workshop. The PI category is fish trader, meat mill, consumen and ice supplier. The P category is “argo rent” or transporter, gallon seller, pudding ice seller or “cendol ice” and vegetables seller. The I category is fisherman, fish seller tricycle. Other categories are “tukang ojek” and water suppliers.